2008
DOI: 10.1177/1098611108327309
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for Policewomen's Assertive and Passive Reactions to Sexual Harassment

Abstract: To understand how constructive responses could be encouraged and supported, research was conducted to show the reasons for female police officers' responses to sexual harassment. A survey was administered in small groups to 117 female officers from 5 law enforcement agencies in a Midwestern state. For the 106 who had experienced harassment in the last 2 years, perceiving sexual harassing behavior as a violation of organizational policy predicted seeing harassing acts as severe, which in turn predicted assertiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 57 publications
1
24
1
Order By: Relevance
“…This notion has been confirmed in past research. For example, in sexual harassment cases, nurturing the independent self is key to responding assertively (Chaiyavej & Morash, 2009). Also, the independent self was found to mediate the relationship between country and advising rape victims to report to the police, where, Americans were more inclined to advise victims than Japanese (Yamawaki, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This notion has been confirmed in past research. For example, in sexual harassment cases, nurturing the independent self is key to responding assertively (Chaiyavej & Morash, 2009). Also, the independent self was found to mediate the relationship between country and advising rape victims to report to the police, where, Americans were more inclined to advise victims than Japanese (Yamawaki, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Chiyavej and Morash (2008) found that, among a sample of 117 female officers from five law enforcement agencies in a Midwestern state, the existence of clear organizational anti-sexual harassment policies significantly predicted perceived severity of harassing acts that in turn predicted assertive reactions (i.e., reporting the incident, expressing displeasure to the offender, rejecting the offender's behavior, and threatening the offender with negative consequences). They also found that the less important the officer's independent participation in decision-making, the higher the concern for social reactions, which significantly predicted passive reactions to harassment (i.e., going along, ignoring or deflecting the attention, changing own behavior, and other avoidance mechanisms) (Chiyavej & Morash, 2008).…”
Section: Influence Of Gender Stereotypes On Employment Patterns and Rmentioning
confidence: 98%
“…This uncertainty of how the advice or support will be considered is one reason why women generally do not seek social support (Bingham & Scherer 1993, Wijayatilake & Zachariya 2000, Haspels et al 2001, Chaiyavej & Morash 2009. Despite this uncertaintly women appear to be sharing infromation in order to caution and advise others.…”
Section: Informational Supportmentioning
confidence: 99%
“…Women are also said to not confide about their experiences with others, even with their family, due to fear of condemnation or criticism, fearing that others will think negatively of them (Haspels et al 2001, Chaiyavej & Morash 2009), fearing that they will not be believed (Bingham & Scherer 1993) Similarly, Tharanga (23 year old, unmarried, clerk) and Nadhini (27 years old, unmarried, executive) are also minority women workers in their branch who knew about each other's experiences although they too were not so close friends. Hence, while emotional support is intentionally sought from close friends, the information about instances of sexual harassment and related incidents is also shared (maybe not with the intention of gaining emotional support, but maybe with the intention of warning others) in certain instances with a few others (like other female co-workers who are a minority in a work setting).…”
Section: Malkamentioning
confidence: 99%
See 1 more Smart Citation